1970
DOI: 10.1111/j.1432-1033.1970.tb01156.x
|View full text |Cite
|
Sign up to set email alerts
|

Enzymes from Human Gastric Mucosa Conferring Blood‐Group A and B Specificities upon Erythrocytes

Abstract: Enzyme preparations obtained from human gastric mucosa microsomes are able to provide human erythrocytes with blood-group A and B specificities, the newly conferred serological properties being dependent on the blood-group of the tissue donor. The time-course and the extent of the enzyme-catalyzed change in antigenic properties of the erythrocytes were assessed by the serum absorption method.The enzyme preparation from gastric mucosa of group A, individuals, when incubated with 0 or B erythrocytes in the prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
22
0

Year Published

1972
1972
2013
2013

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 62 publications
(22 citation statements)
references
References 16 publications
0
22
0
Order By: Relevance
“…The N-acetyl-D-galactosaminyltransferase determined by the blood group A gene has been found in soluble form in human milk (1,2) and tnembrane-bound in human submaxillary gland (3), human gastric mucosa (4,5), hog submaxillary gland (6,7), and hog gastric mucosa (8)(9)(10). This transferase has been found recently in human ovarian cyst linings and fluids (11).…”
mentioning
confidence: 98%
“…The N-acetyl-D-galactosaminyltransferase determined by the blood group A gene has been found in soluble form in human milk (1,2) and tnembrane-bound in human submaxillary gland (3), human gastric mucosa (4,5), hog submaxillary gland (6,7), and hog gastric mucosa (8)(9)(10). This transferase has been found recently in human ovarian cyst linings and fluids (11).…”
mentioning
confidence: 98%
“…Since the same gene appears to specify blood-type-A of erythrocytes as well as of body secretions [2], the gene-dependent enzyme must be able to transfer a-acetylgalactosaminyl residues to bloodgroup-A precursor molecules of glycolipid as well as of glycoprotein nature. In a previous investigation it has been shown that an enzyme, which was obtained from the gastric mucosa of group-A individuals and was found to transfer acetylgalactosamine residues onto water-soluble blood-group substances, was also capable of conveying blood-group-A specificity upon 0-erythrocytes [3]. Red cells of bloodgroup 0, when incubated with UDP-N-acetyl-Dgalactosamine in the presence of this enzyme, acquired the serological characteristics of A,-cells.…”
mentioning
confidence: 99%
“…According to the hypothesis proposed by Watkins and Morgan (32,33), addition of the specific sugar to the H antigen yields A or B antigen. The isolation of specific glycosyltransferases from human tissues, which transform H antigen to A or B antigen, supported their hypothesis (23,25,34) . The production of precursor H antigen without subsequent transformation into the complete A or B specificity and independent production of either A or B antigen in AB individuals could be due to a lack of the specific glycosyltransferases or lack of specific sugar.…”
Section: Discussionmentioning
confidence: 60%